2018
DOI: 10.1002/pon.4761
|View full text |Cite
|
Sign up to set email alerts
|

Latent class analysis differentiation of adjustment disorder and demoralization, more severe depressive and anxiety disorders, and somatic symptoms in patients with cancer

Abstract: In contrast with the severe symptom cluster carrying anhedonia, anxiety, and demoralization, the moderate symptom cluster was formed by patients with demoralization and impaired functioning, a clinical picture consistent with a unidimensional model of adjustment disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
40
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 29 publications
9
40
0
2
Order By: Relevance
“…This perspective would not understand existential distress‐adjustment disorder as a “subthreshold problem” (hierarchically only diagnosed when criteria for depressive or anxiety disorders are not fully met) but a distinct entity that can be related to intense suffering. It is also coherent with the findings of Bobevski et al, indicating a distinct and significant subgroup (13%) with moderate demoralization, significant functional impairment and increased risk for suicidal ideation. Two dominant symptom clusters of adjustment difficulty could exist: (1) worried preoccupation with what could happen in an excessive attempt to control and (2) the disheartened despair about what cannot happen.…”
Section: What Is the Threshold For Clinically Relevant Existential DIsupporting
confidence: 91%
See 1 more Smart Citation
“…This perspective would not understand existential distress‐adjustment disorder as a “subthreshold problem” (hierarchically only diagnosed when criteria for depressive or anxiety disorders are not fully met) but a distinct entity that can be related to intense suffering. It is also coherent with the findings of Bobevski et al, indicating a distinct and significant subgroup (13%) with moderate demoralization, significant functional impairment and increased risk for suicidal ideation. Two dominant symptom clusters of adjustment difficulty could exist: (1) worried preoccupation with what could happen in an excessive attempt to control and (2) the disheartened despair about what cannot happen.…”
Section: What Is the Threshold For Clinically Relevant Existential DIsupporting
confidence: 91%
“…Also, symptom classification studies point towards a differentiation of anhedonia and demoralization . Applying latent class differentiation, Bobevski et al found that demoralization was present in two groups, where one had severe symptoms of anxiety and depression with high levels of demoralization (10%) and the second was characterized by moderate demoralization and low anxiety and depression (13%). These results are coherent with the idea that demoralization can occur independently and also as a result of high levels of depression and anxiety.…”
Section: The Comorbidity Of Existential Distress With Anxiety and Depmentioning
confidence: 99%
“…The cited data within literature vary between 40% and 77%. Bobevsky et al (2018) reported a higher proportion of 54.3% for a subgroup characterized by the absence of distress in a German cancer patient sample.…”
Section: Discussionmentioning
confidence: 98%
“…Insbesondere in der Phase der Ambivalenz (. 13,9-30,2 % der befragten onkologischen Patienten Suizidgedanken bejahten [2].…”
Section: Präsuizidale Entwicklungunclassified